A Microservice-Based System for Industrial Internet of Things in Fog-Cloud Assisted Network - Khoso, F. H.; Lakhan, A.; Arain, A. A.; Soomro, M. A.; Nizamani, S. Z.; Kanwar, K. (Engineering, Technology & Applied Science Research, 2021)
Nowadays, the usage of the Industrial Internet of Things (IIoT) in practical applications has increased. The primary utilization is a fog cloud network, which offers different services, such as network and remote edges, at different places. Existing studies implemented the Service-Oriented Architecture (SOA) based on the fog-cloud network to run IIoT applications, such as e-healthcare, e-agriculture, renewable energy, etc. However, due to the applications’ monolithic property, issues like failures, security, and cost factors occur, e.g. the failure of one service in SOA affects monolithic applications’ performance in the system. With this motivation, this study suggests a microservice-based system to deal with the cost, security, and failure risks of IIoT applications in the fog-cloud system. The study improves the existing SOA systems for e-healthcare, e-agriculture, and renewable energy and minimizes the applications’ overall cost. The performance evaluation shows that the devised systems outperform the existing SOA system in terms of failure, cost, and the deadline for all applications.